Classification of Turkish safflower oils based on their fatty acid and sterol profiles using multivariate techniques - Yorulmaz, Asli (Array, 2019)
The aim of the current study was to classify Turkish safflower oils based on sterol and fatty acid composition. For this purpose, 37 samples from five different safflower varieties (Dinçer, Linas, Remzibey-05, Balcı and Olas) grown in the same agricultural and environmental conditions were obtained. Seeds were evaluated for their oil, water and ash content. Oils of seeds were extracted by solvent extraction and oils were analyzed for their sterols and fatty acids. Results have shown that Linas and Olas varieties’ oil contents were significantly higher than others’. There were clear differences in fatty acid compositions of various cultivars. Remzibey-05 and Olas varieties were different from others by their higher oleic and relatively lower linoleic acid ratios. Total sterol contents of oils ranged among 2700-3626 mg/kg and the main phytosterol was β-sitosterol covering 43.27-48.16 % of the total sterols.